Hubungan Asupan Serat Dengan Kadar Kolesterol Pada Penderita Penyakit Jantung Koroner Rawat Jalan Di RSUD Dr. Moewardi Surakarta - DEWI, Selly Shinta, Nur Lathifah Mardiyati, S.Gz., M.S, Elida Soviana, S.Gz., M.Gizi (2015)
Introduction: Coronary Heart Disease (CHD) is still the highest cause of death in Indonesia. The risk factors that contribute to the incidence of CHD is the risk factors that can not be modified (age, sex, gender) and the risk factors that can be modified (smoking, dyslipidemia, hypertension, obesity, lack of physical activity, diabetes mellitus). Intake of fiber can reduce cholesterol levels by reabsorsing bile in the body, so it can reduce the availability of cholesterol and cholesterol in the blood stream can be reduced. Objective: This study aimed to determine the relationship between fiber intake with cholesterol level in CHD outpatients at Dr. Moewardi Hospital of Surakarta. Methods: The research was an observational design with cross-sectional design. The number of respondents this study amounted to 24 respondents with sequential sampling technique of random sampling. Data collection was conducted in 24 hour recall for 4 days to respondents. The statistical test used Pearson Product Moment tests. Results: The results showed that most respondents had good fiber intake (91.7%) and good cholesterol (95.7%).Statistical test of the relationship between the two variables was obtained with r = 0.035 with significance (p) value of 0.872. Value (p) > 0.05 means that the test was not significant ( H0 ) . Conclusion: There was no significant association between fiber intake and cholesterol level inCHD outpatients at Dr. Moewardi Hospital of Surakarta. Keywords: fiber intake, cholesterol levels, CHD Bibliography: 34 : 2001 - 2012